Surfaces and Interfaces in Natural Fibre Reinforced Composites Fundamentals, Modifications and Characterization - Le Moigne, Nicolas; Otazaghine, Belkacem; Corn, Stéphane; Angellier-Coussy, Hélène; Bergeret, Anne (Biobased Polymers, 2018)
This book is addressed to Master and PhD students as well as researchers from academia and industry. It aims to provide the key definitions to understand the issues related to interface modifications in natural fibre based composites considering the particular supramolecular and micro- structures encountered in plant fibres. A particular emphasis is given to the modification and functionalization strategies of natural fibres and their impact on biocomposites behaviour and properties. Commonly used and newly developed treatment processes are described in view of scaling-up natural fibre treatments for their implementation in industry. Finally, a detailed and comprehensive description of the tools and methodologies developed to investigate and characterize surfaces and interfaces in natural fibre based composites is reviewed and discussed.